Meta-analysis of Outcomes Using Ceftolozane-Tazobactam and Ceftazidime-Avibactam for Multidrug-Resistant Organism Infections. (October 2020) - Wilson, Geneva; Fitzpatrick, Margaret; Walding, Kyle; Gonzalez, Beverly; Evans, Charlesnika
Abstract : Background: Ceftolozane-tazobactam (C/T) and ceftazidime-avibactam (C/A) are new β-lactam/β-lactamase combination antibiotics that were approved by the FDA in 2014 and 2015, respectively, to treat complicated intra-abdominal and urinary tract infections. They are commonly used to treat multidrug-resistant Pseudomonas aeruginosa (MDRPA) and carbapenem-resistant Enterobacteriaceae (CRE) infections at any site. Both medications are also often used as salvage therapy when empiric therapy has failed or when the infectious organism tests resistant to all other available antibiotics. The purpose of this review is to present the clinical experience and reported clinical success rates of C/T and C/A. Methods: PubMed, EMBASE, and Google Scholar were searched from January 1, 2013, through October 1, 2019, for publications detailing clinical experience with C/T and C/A in patients with CRE and MDRPA infections. Included study designs were extended cases series and clinical observational studies. Information on infection type, bacterial agent, salvage therapy uses, clinical success, and resistance development during treatment were abstracted. Meta-regression analysis was used to determine the pooled effectiveness of C/T and C/A among included studies. Results: The literature search returned 1, 645 publications. After exclusion criteria were applied, 16 publications representing 769 patients were retained. The study population was mostly male (pooled average, 62%). The major comorbidities represented in the pooled population were solid organ transplantation (20.0%), kidney disease (19.5%), cardiovascular disease (15.3%), and diabetes (15.3%). Pneumonia was the predominant infection type (41.4%) and MDRPA was the pathogen most frequently evaluated (57.7%). The pooled clinical success rate was 70.2% (95% CI, 64.5%–75.3%). Also, 10 studies explicitly evaluated C/A or C/T as salvage therapy. The pooled clinical success rate for salvage therapy studies was 75.2% (95% CI, 69.7%–80.0%). Development of resistance to C/T or C/A during or after treatment was reported for 2.0% of the population. Conclusion: Overall, these medications have a high clinical success rate in patients with severe and complicated infections and limited treatment options. Pooled clinical success rates were high (70.2%) and the medications were particularly effective as salvage therapy. Resistance rates were low, although this could have been biased by the small percentage of studies that reported on this outcome. More longitudinal studies comparing the effectiveness of C/T and C/A against other antibiotic regimens are needed. Funding: None Disclosures: None